Pendampingan Masyarakat Nagari Batahan Jorong Sawah Mudik dalam Pembangunan Mesjid Taqwa : Perencanaan dan Desain Mesjid - Mutia Alius; Barkhia Yunas; Yuni Purnama Syafri; Dyla Midya Octavia; Wiwin Putri Zayu; Fahma Furqani; Juli Adevia; Juwita Wirta Sri Depi; Rehan Putra Saira; Muhammad Nabil Riansyah (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
Taqwa Mosque in Jorong Sawah Mudik, Nagari Batahan Utara, Pasaman Barat Regency, plays a significant role as a center for worship, education, and social activities in the community. However, over time, the mosque's condition has become inadequate to meet the growing needs of its congregation. This study aims to redesign and develop the mosque with an earthquake-resistant structural concept using caisson foundations. The methods employed include data collection, spatial needs analysis, structural design using AutoCAD and ETABS applications, and participatory discussion forums with the local community. The result is an optimal mosque design that considers spatial efficiency, accessibility, and sustainability. This study highlights the importance of community involvement in creating a design that is not only functional but also aligned with local values.